Caffeine prevents hypoxia-induced dysfunction on branchial bioenergetics of Nile tilapia through phosphoryl transfer network - Baldissera M.D. (2019)
© 2018 Elsevier B.V.Hypoxia is a critical issue in aquaculture of marine or freshwater fishes especially in intensive aquaculture systems, contributing to severe economic losses for fish producers. Some evidence has suggested the involvement of phosphoryl transfer network, catalyzed by creatine kinase (CK), pyruvate kinase (PK) and adenylate kinase (AK) in the metabolic alterations during exposure to hypoxia, but the effects on fish exposed to acute hypoxia remains unknown. Moreover, some evidence has revealed the protective effects of caffeine supplementation against hypoxia, including linked to energetic status. Therefore, the aim of this study was to evaluate whether diet supplemented with caffeine (5 and 8%) is able to protect the gills against bioenergetics dysfunction on Nile tilapia exposed to hypoxia. Branchial cytosolic and mitochondrial CK, and sodium-potassium pump (Na+, K+-ATPase) activities were inhibited in fish exposed to hypoxia compared to control group, while branchial AK and lactate dehydrogenase (LDH) activities and lactate levels were stimulated. The use of 8% dietary caffeine was able to prevent all alterations induced by exposure to hypoxia, with exception of the inhibition on Na+, K+-ATPase activity. The lower activity to both CK fractions (cytosolic and mitochondrial) contributes to impairment on bioenergetic homeostasis, while augmentation on AK activity can be considered an attempt to prevent or reduce the energetic imbalance during hypoxia. Also, the use of 8% dietary caffeine prevented alteration energetic metabolism, as well as occurrence of anaerobic metabolism. In summary, use of 8% dietary caffeine can be an alternative to improve branchial energetic homeostasis during exposure to hypoxia.